Employees' Perspectives About Rewards and Incentives: Are They Overrated: Exploring the Impact of Employee Perspectives on Rewards and Incentives (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Employees today aremore concerned about the rewards practices on in which they seek for the groundelements which should be demonstrated in accordance to ensure that theorganizational reward system will be as effective as possible. This study aimsto investigate the relationship between the perception of the employees onfairness, transparency, controllability and the reward values of the rewardpractices. The reward values may not only be in monetary form but it can alsobe alternatively provided in other forms such as employer appraise to theemployee. This paper also aims to analyze whether the employee’s perspectiveabout the rewards and incentives are overrated.